Robust Optimization of the Delta Parallel Robot - Lara-Molina, Fabian A.; Lobato, Fran Sérgio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper addresses the robust optimization of the Delta parallel robot based on multi-objective optimization. The dimensional tolerances of the geometric parameters and their effect on the kinematic error are considered. The objective functions for the optimization are based on kinematic indices and the errors in the active joint. These indices are evaluated over a required workspace in the parallel manipulator’s complete workspace. Moreover, the sensitivity of the dimensional tolerance on the kinematic accuracy is analyzed. The set of optimal solutions for the Delta robot to optimize the kinematic performance and minimize the effect of dimensional tolerance is obtained from the solutions of robust optimization.